2008
DOI: 10.1143/jjap.47.212
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxations in the Ce1-xYbxO2-δ System

Abstract: The dielectric properties of Yb-doped CeO2 (Ce1-xYbxO2-δ) which is an oxide-ion conductor were investigated. Numerical analysis of the frequency dependences of dielectric constants (ε') and dielectric loss factors (ε'') revealed that the dielectric characteristics can be successfully explained by the superimposition of both Debye-type polarization due to dopant-vacancy associates and electrolyte–electrode interfacial polarization. The temperature response of the dielectric properties was less active than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The dielectric constant of oxide-ion conductors was composed of both Debye type polarization and electrode-electrolyte interfacial polarization which depends on the inverse of frequency [20]. The apparent dielectric constant (ε ) can be given as in the following equation, assuming the presence of various dipoles with multiple relaxation times [24];…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constant of oxide-ion conductors was composed of both Debye type polarization and electrode-electrolyte interfacial polarization which depends on the inverse of frequency [20]. The apparent dielectric constant (ε ) can be given as in the following equation, assuming the presence of various dipoles with multiple relaxation times [24];…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has reported that the two kinds of dipole polarizations were observed in 9 mol% Relationship between activation energy estimated from relaxation frequency and electrical conductivity were discussed in our other published paper [6]. Figure 5 shows a frequency dependence of σ ac for the sample with x = 0.2 in the temperature of 673 to 1173 K, where the large dispersion was observed.…”
Section: Resultsmentioning
confidence: 80%
“…Our research group reported that the relationship between oxide ion conduction and dielectric relaxation from the viewpoints of dielectric constant, dielectric loss factor and loss tangent (tanδ) in the Sm, Nd, or Yb doped CeO 2 [4][5][6] and Y or Ca stabilized ZrO 2 [7,8] systems. According to those studies, the dielectric properties of oxide ion conductors can be explained by the superposition of Debye-type polarization due to the dopant-vacancy associates [Ln Ce ′-V O¨] ‧ (Ln: dopant cation) and charge current on electrolyte-electrode interface.…”
Section: Introductionmentioning
confidence: 99%
“…The detail explanations concerning the theoretical treatment of dielectric properties for oxide-ion conductors are given elsewhere [5][6][7][8][9][10]. Therefore, the apparent dielectric constant (ε r ′) can be given by the following equation (1), assuming the presence of various Debye-type dipoles with multiple relaxation times: (1) where ω, ε r0i , and τ i represent the angular frequency (=2πf), the dielectric constant at the low frequency limit due to the i-th Debye-type polarization and the i-th dipole relaxation time (=1/2πf i ), respectively.…”
Section: Transaction Of the Materials Research Society Of Japanmentioning
confidence: 99%
“…Then, we paid attention to the dielectric properties of oxide-ion conductor, in order to reveal the polarization mechanism of the oxide-ions and the vacancy-dopant pairs. Recently, the group of present authors have clarified that the frequency dependence of dielectric constant (ε r ′) and dielectric loss factors (ε r ″) in the Ca, Nd, Sm, or Yb-doped CeO 2 systems, which are typical oxide ion conductor [5][6][7][8]. It was revealed that the dielectric properties can be made up of Debye-type polarization due to dopant-vacancy associates [Ca zr ″-V o¨] and interfacial polarization of electrolyte-electrode.…”
Section: Introductionmentioning
confidence: 99%